2019
DOI: 10.3892/mmr.2019.10505
|View full text |Cite
|
Sign up to set email alerts
|

Identification of driver genes and key pathways of prolactinoma predicts the therapeutic effect of genipin

Abstract: The purpose of the present study was to identify the potential targets and markers for diagnosis, therapy and prognosis in patients with prolactinoma at the molecular level and to determine the therapeutic effects of genipin in prolactinoma. The gene expression profiles of GSE2175, GSE26966 and GSE36314 were obtained from the Gene Expression Omnibus database. The differentially expressed genes (DEGs) were identified after comparing between gene expression profiles of the prolactinoma tissues and normal tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
3
0
1
Order By: Relevance
“…Zhong et al reported that, in prolactinoma cells, genipin upregulated the expression levels of EGR1 and p21 (a downstream mediator of EGR1), with EGR1 inhibiting the proliferation, migration, and induction of prolactinoma cell apoptosis [ 75 ].…”
Section: Effects Of Genipin On Various Cancersmentioning
confidence: 99%
“…Zhong et al reported that, in prolactinoma cells, genipin upregulated the expression levels of EGR1 and p21 (a downstream mediator of EGR1), with EGR1 inhibiting the proliferation, migration, and induction of prolactinoma cell apoptosis [ 75 ].…”
Section: Effects Of Genipin On Various Cancersmentioning
confidence: 99%
“…The selected genes between HSYA and ISFA were input into the STRING (https:// string-db.org/ (accessed on 22 January 2022)) database [26] for protein-protein interaction (PPI) network analysis. Proteins at a minimum required interactions with a confidence score ≥ 0.9.…”
Section: Construction Of the Protein-protein Interaction Networkmentioning
confidence: 99%
“…Zhang et al [ 54 ] suggest that genipin (1, 1.25, and 5 mg/kg) protects against LPS-induced acute lung injury by inhibiting the NFκB and NLR family pyrin domain containing 3 (NLRP3) signaling pathways in mice. In addition, 2 and 5 mg/kg genipin appears to protect against apoptosis and inflammation in LPS-induced acute lung injury by promoting autophagy [ 55 ].…”
Section: Other Biological Properties Of Genipinmentioning
confidence: 99%